Ethical dimensions and societal implications: ensuring the social responsibility of CRISPR technology - Biswas, Irfan (Frontiers in Genome Editing, 2025)
CRISPR-Cas9 is a breakthrough genome-editing platform that can cut chosen DNA sequences with unprecedented speed, accuracy, and affordability. By reprogramming a single guide RNA, researchers now alter gene function, correct pathogenic variants, or introduce novel traits. Earlier tools such as zinc-finger nucleases and TALENs performed similar tasks but were significantly more complex and costly. Yet CRISPR’s very power raises urgent ethical concerns: Who controls its use, and how can society prevent germ-line enhancement, eugenic selection, or unequal access that favors wealthy nations and patients? A well-publicized case of embryo editing already showed how premature, unregulated experiments can erode public trust. This perspective therefore frames CRISPR’s scientific promise alongside its social responsibilities, arguing that proactive, globally coordinated governance is essential to unlock benefits while preventing new forms of genetic inequality.